An Industry 4.0 Conceptual Model Proposal for Cable Harness Testing Equipment Industry - Rosa, Elisa Soares (2022)
Nowadays, consumers search for organizations that can provide customized services at affordable prices. Therefore, it becomes essential for companies to meet those requirements by creating flexible and resilient production systems. Technological pathways such as industry 4.0 can represent a positive impact in the creation of those systems, through the integration of smart processes and technologies that can contribute to the automation of several activities within the shopfloor. Electrically controlled functions in passenger, commercial and special vehicles are becoming increasingly complex. If the signal and power cables were to be damaged, the vehicle’s operation would be affected, resulting in quality issues that can have a direct impact on safety, which can negatively affect the manufacturer’s reputation. Automotive manufacturers are thriving to achieve ever-growing mass customization, by offering a wide range of products, allowing for all clients to fulfill their needs. This scenario puts heavy pressure upon the cable harness industry, which must be as flexible as possible to supply all types of cables required by the automotive industry. This pressure is also extended to the enterprises that build test equipment for cable harnesses. In this context, the research group was able to plan an Industry 4.0 Network of Solutions that meets the requirements of the machining process of a cable harness testing equipment company, while compensating its flaws and optimizing it. The network is expected to promote the reduction of production cycle times in multiple activities, resulting in a production process that is expected to be more efficient and less prone to flaws.